PERAN GURU DALAM MENGGUNAKAN MEDIA BUKU CERITA BERGAMBAR UNTUK MENSTIMULASI KEMAMPUAN BERBICARA PADA ANAK USIA 4-6 TAHUN DI TK CAHAYA MENTARI PONTIANAK KOTA - Elvu, Elvu Elvu; Miranda, Dian Miranda; Lukmanulhakim, Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to describe how teachers utilize picture storybooks as a medium to stimulate the speaking skills of children aged 4-6 years at TK Cahaya Mentari, Pontianak Kota. The research employs a qualitative descriptive method. The subjects of the study consist of three teachers and children aged 4-6 years at the kindergarten. Data collection techniques include interviews, observations, and documentation. Data analysis follows several stages: data collection, data reduction, data presentation, and conclusion drawing. The validity of the data is ensured through triangulation and member checking. The findings indicate that teachers play a crucial role in selecting picture storybooks by considering the simplicity of words, the clarity of illustrations, and the use of easily understandable language. Furthermore, the selected books are designed to enhance children's vocabulary acquisition by incorporating readable fonts and a simple writing style. Teachers also use picture storybooks to support children's sentence formation skills by ensuring language appropriateness and a writing style that encourages the construction of sentences with more than two words, enabling children to begin effective communication. The study concludes that the role of teachers in utilizing picture storybooks is relatively effective in stimulating children's speaking abilities, though further improvements are needed. Therefore, it is recommended that teachers optimize the use of picture storybooks to enhance children's pronunciation and sentence construction skills, thereby fostering better communication development.